2020
DOI: 10.1186/s12885-020-6690-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with initially locally advanced pancreatic adenocarcinoma who did not benefit from resection: a prospective cohort study

Abstract: Background: The current study aimed to evaluate the outcomes of patients with unresectable non-metastatic locally advanced pancreatic adenocarcinoma (LAPA) who did not benefit from resection considering the treatment strategy in the clinical settings. Methods: Between 2010 and 2017, a total of 234 patients underwent induction chemotherapy for LAPA that could not be treated with surgery. After oncologic restaging, continuous chemotherapy or chemoradiation (CRT) was decided for patients without metastatic diseas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…3,[30][31][32] One study compared FFX followed by CRT or chemotherapy alone, and as in our study, outcomes were improved with the addition of CRT. 33 A single-arm study of 50 patients in Italy with neoadjuvant FFX and SBRT reported that SBRT delivery to the 39 patients without progression after FFX was associated with a significantly improved median OS (18 months in the SBRT group vs 5 months in the non-SBRT group). 34 After SBRT, seven patients had an RO resection and experienced a significantly better 3-year OS than nonresected patients (43% vs 6.5%).…”
Section: Discussionmentioning
confidence: 99%
“…3,[30][31][32] One study compared FFX followed by CRT or chemotherapy alone, and as in our study, outcomes were improved with the addition of CRT. 33 A single-arm study of 50 patients in Italy with neoadjuvant FFX and SBRT reported that SBRT delivery to the 39 patients without progression after FFX was associated with a significantly improved median OS (18 months in the SBRT group vs 5 months in the non-SBRT group). 34 After SBRT, seven patients had an RO resection and experienced a significantly better 3-year OS than nonresected patients (43% vs 6.5%).…”
Section: Discussionmentioning
confidence: 99%
“…a single infusion of FOLFIRINOX). Due to the recent advancement in neoadjuvant therapy regimen, patients with LAPC would in particular profit from a more detailed therapy monitoring since in this patient collective neoadjuvant induction therapy aims at conversion to a resectable tumor stage [ 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of radiation therapy and chemotherapy is not recommended, as it has not demonstrated any survival advantages [ 12 , 13 ]. Unfortunately, most of these patients have a very limited chance of undergoing surgery even after chemotherapy [ 14 ]. In this context, pain management has an important place.…”
Section: Pancreatic Cancer Generalitiesmentioning
confidence: 99%